Relay Feedback Analysis, Identification and Control - Wang, Qing-Guo; Lee, Tong Heng; Lin, Chong (Springer London, 2003)
Relay feedback has attracted considerable research attention for more than a century but there has been no recent summary of the many newly-developed tools and results now available for this important area as a whole, those that have been published tending to focus on one process or controller type only. Relay Feedback is divided into three parts, the first of which is devoted to the analysis of relay feedback systems within a general setting with information on: existence of solutions; existence of limit cycles; local and global stability of limit cycles; limit cycles with more than two switchings per period; plants with time delay; relays with asymmetric hysteresis. The second part, on the improvement of process identification shows the reader how to: modify a standard relay to provide better excitation of a process at a number of important frequencies; devise new algorithms designed to make better use of information from relay feedback tests. The book's third part is a presentation of recent developments in control design providing: a unified framework for the design of internal-model, proportional-integral-derivative or general-single-loop controllers for SISO or MIMO systems with or without time delays; characterisation of time delays and non-minimum phase zeros for closed-loop systems. Relay Feedback presents a comprehensive, up-to-date and detailed treatment of relay feedback theory, the use of relay feedback for process identification and the use of identified models for general control design in a single volume. The work assumes only knowledge of linear system theory on the part of the reader and should therefore be of use to graduate students and practising engineers as well as to researchers